Geographic patterns of biodiversity in European coastal marine benthos. (14th September 2016) - Hummel, Herman; Van Avesaath, Pim; Wijnhoven, Sander; Kleine-Schaars, Loran; Degraer, Steven; Kerckhof, Francis; Bojanic, Natalia; Skejic, Sanda; Vidjak, Olja; Rousou, Maria; Orav-Kotta, Helen; Kotta, Jonne; et al.
Abstract : Within the COST action EMBOS (European Marine Biodiversity Observatory System) the degree and variation of the diversity and densities of soft-bottom communities from the lower intertidal or the shallow subtidal was measured at 28 marine sites along the European coastline (Baltic, Atlantic, Mediterranean) using jointly agreed and harmonized protocols, tools and indicators. The hypothesis tested was that the diversity for all taxonomic groups would decrease with increasing latitude. The EMBOS system delivered accurate and comparable data on the diversity and densities of the soft sediment macrozoobenthic community over a large-scale gradient along the European coastline. In contrast to general biogeographic theory, species diversity showed no linear relationship with latitude, yet a bell-shaped relation was found. The diversity and densities of benthos were mostly positively correlated with environmental factors such as temperature, salinity, mud and organic matter content in sediment, or wave height, and related with location characteristics such as system type (lagoons, estuaries, open coast) or stratum (intertidal, subtidal). For some relationships, a maximum (e.g. temperature from 15–20°C; mud content of sediment around 40%) or bimodal curve (e.g. salinity) was found. In lagoons the densities were twice higher than in other locations, and at open coasts the diversity was much lower than in other locations. We conclude that latitudinal trends and regional differences in diversity and densities are strongly influenced by, i.e. merely the result of, particular sets and ranges of environmental factors and location characteristics specific to certain areas, such as the Baltic, with typical salinity clines (favouring insects) and the Mediterranean, with higher temperatures (favouring crustaceans). Therefore, eventual trends with latitude are primarily indirect and so can be overcome by local variation of environmental factors.